Longitudinal Impacts of Forest Loss on Bartonella and Hemotropic Mycoplasma Dynamics in Vampire Bats Within a Fragmented Habitat - Lauren R. Lock; Kristin E. Dyer; Dmitriy V. Volokhov; Anni Yang; M. Brock Fenton; Nancy B. Simmons; Daniel J. Becker (Molecular Ecology, 2026)
Habitat fragmentation can negatively impact wildlife, including increasing infectious disease risk. We assessed spatiotemporal changes in pathogen dynamics in vampire bats ( Desmodus rotundus ) in response to habitat fragmentation using general linear mixed models to investigate the influence of site, year, and tree cover on Bartonella spp. and hemotropic Mycoplasma spp. (hemoplasmas) infection risk in bats in one large and one small forest fragment in Belize across seven years. While Bartonella infections were more likely in the final years of the study regardless of site, hemoplasma infection likelihood was not significantly different across years or sites. Bartonella infections were associated with increased forest loss in the large fragment only, whereas hemoplasma infections were not associated with forest loss. The effects of site, year, and forest loss on infection likelihood varied by pathogen genotype despite low model explanatory power. Neither site nor year was associated with bartonellae, but one genotype was positively associated with tree cover. Two hemoplasmas were influenced by year with differing trends: one genotype was negatively associated with tree loss across sites, while another was positively associated with forest loss at the small fragment only. Both pathogens were similarly influenced by bat demographics and showed instances of infection status and genotype switching. Our work suggests that the effects of habitat fragmentation on infection risk depend on both the pathogen and specific genotype, complicating expectations of how environmental change affects wildlife disease dynamics. Efforts to mitigate infectious disease impacts in fragmented systems should be tailored to specific pathogens of concern.

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

FDA-approved disulfiram as a novel treatment for aggressive leukemia - Mawar Karsa; Lin Xiao; Emma Ronca; Angelika Bongers; Dayna Spurling; Ayu Karsa; Sandra Cantilena; Anna Mariana; Tim W. Failes; Greg M. Arndt; Laurence C. Cheung; Rishi S. Kotecha; et al. (Journal of Molecular Medicine, 2024)
Acute leukemia continues to be a major cause of death from disease worldwide and current chemotherapeutic agents are associated with significant morbidity in survivors. While better and safer treatments for acute leukemia are urgently needed, standard drug development pipelines are lengthy and drug repurposing therefore provides a promising approach. Our previous evaluation of FDA-approved drugs for their antileukemic activity identified disulfiram, used for the treatment of alcoholism, as a candidate hit compound. This study assessed the biological effects of disulfiram on leukemia cells and evaluated its potential as a treatment strategy. We found that disulfiram inhibits the viability of a diverse panel of acute lymphoblastic and myeloid leukemia cell lines ( n = 16) and patient-derived xenograft cells from patients with poor outcome and treatment-resistant disease ( n = 15). The drug induced oxidative stress and apoptosis in leukemia cells within hours of treatment and was able to potentiate the effects of daunorubicin, etoposide, topotecan, cytarabine, and mitoxantrone chemotherapy. Upon combining disulfiram with auranofin, a drug approved for the treatment of rheumatoid arthritis that was previously shown to exert antileukemic effects, strong and consistent synergy was observed across a diverse panel of acute leukemia cell lines, the mechanism of which was based on enhanced ROS induction. Acute leukemia cells were more sensitive to the cytotoxic activity of disulfiram than solid cancer cell lines and non-malignant cells. While disulfiram is currently under investigation in clinical trials for solid cancers, this study provides evidence for the potential of disulfiram for acute leukemia treatment. Key messages Disulfiram induces rapid apoptosis in leukemia cells by boosting oxidative stress. Disulfiram inhibits leukemia cell growth more potently than solid cancer cell growth. Disulfiram can enhance the antileukemic efficacy of chemotherapies. Disulfiram strongly synergises with auranofin in killing acute leukemia cells by ROS induction. We propose testing of disulfiram in clinical trial for patients with acute leukemia.

Detection of human adenovirus F41 in wastewater and its relationship to clinical cases of acute hepatitis of unknown aetiology - Marina I. Reyne; Danielle M. Allen; Ashley Levickas; Pearce Allingham; Jonathan Lock; Arthur Fitzgerald; Cormac McSparron; Behnam F. Nejad; Jennifer McKinley; Andrew Lee; Stephen H. Bell; Joshua Quick; et al. (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Hemodynamic Effects of Lipid-Based Oxygen Microbubbles via Rapid Intravenous Injection in Rodents - Katherine J. Black; Andrew T. Lock; Lindsay M. Thomson; Alexis R. Cole; Xiaoqi Tang; Brian D. Polizzotti; John N. Kheir (Pharmaceutical Research, 2017)

Amino acid composition, protein content, and nitrogen-to-protein conversion factors of 21 seaweed species from Norwegian waters - I. Biancarosa; M. Espe; C. G. Bruckner; S. Heesch; N. Liland; R. Waagbø; B. Torstensen; E. J. Lock (Journal of Applied Phycology, 2017)

Inter-laboratory study of human in vitro toxicogenomics-based tests as alternative methods for evaluating chemical carcinogenicity: a bioinformatics perspective - R. Herwig; H. Gmuender; R. Corvi; K. M. Bloch; A. Brandenburg; J. Castell; L. Ceelen; C. Chesne; T. Y. Doktorova; D. Jennen; P. Jennings; A. Limonciel; et al. (Archives of Toxicology, 2016)

Edward Armitage Robinson 1921 – 2013 - J. M. Lock (Kew Bulletin, 2015)

The diurnal cycle of marine cloud feedback in climate models - Mark J. Webb; Adrian P. Lock; Alejandro Bodas-Salcedo; Sandrine Bony; Jason N. S. Cole; Tsuyoshi Koshiro; Hideaki Kawai; Carlo Lacagnina; Frank M. Selten; Romain Roehrig; Bjorn Stevens (Climate Dynamics, 2015)

Transcriptomic alterations induced by Ochratoxin A in rat and human renal proximal tubular in vitro models and comparison to a rat in vivo model - Paul Jennings; Christina Weiland; Alice Limonciel; Katarzyna M. Bloch; Robert Radford; Lydia Aschauer; Tara McMorrow; Anja Wilmes; Walter Pfaller; Hans J. Ahr; Craig Slattery; Edward A. Lock; et al. (Archives of Toxicology, 2012)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Reproduction in an invasive exotic catfish Pterygoplichthys disjunctivus in Volusia Blue Spring, Florida, U.S.A. - M. A. Gibbs; J. H. Shields; D. W. Lock; K. M. Talmadge; T. M. Farrell (Journal of Fish Biology, 2008)
Morphology and reproductive strategies of a population of invasive loricariid catfish, Pterygoplichthys disjunctivus , in Volusia Blue Spring, Florida, were examined using morphological characters, gonado‐somatic indices and batch fecundity. This species has cystovarian ovaries, a left ovary that is significantly larger than the right ovary, and is highly fecund. Ovaries contained multiple oocyte size classes and completely spent females were not found, both of which indicate that this species is a multiple spawner. Reproductive patterns changed significantly between the first (2005) and the last (2007) years of this study; female fish became capable of spawning at a smaller size, a greater proportion of the captured population were capable of spawning each year and female batch fecundity increased, as did male and female gonado‐somatic indices. Plasticity of P. disjunctivus reproductive patterns is discussed in relation to resource availability and environmental stability.

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Distribution of corticotectal cells in macaque - T. M. Lock; J. S. Baizer; D. B. Bender (Experimental Brain Research, 2003)

Effects of Mining Activities on Heavy Metal Concentrations in Water, Sediment, and Macroinvertebrates in Different Reaches of the Pilcomayo River, South America - A. J. P. Smolders; R. A. C. Lock; G. Van der Velde; R. I. Medina Hoyos; J. G. M. Roelofs (Archives of Environmental Contamination and Toxicology, 2003)

The role of glutathione S-transferase- and cytochrome P450-dependent metabolism in the olfactory toxicity of methyl iodide in the rat - M. P. Chamberlain; E. A. Lock; B. A. Gaskell; C. J. Reed (Archives of Toxicology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)